Do green roofs cool the air?. (January 2017) - Solcerova, Anna; van de Ven, Frans; Wang, Mengyu; Rijsdijk, Michiel; van de Giesen, Nick
Abstract: Rapid urbanization and an increasing number and duration of heat waves poses a need to mitigate extremely high temperatures. One of the repeatedly suggested measures to moderate the so called urban heat island are green roofs. This study investigates several extensive sedum-covered green roofs in Utrecht (NL) and their effect on air temperature right above the roof surface. The air temperature was measured 15 and 30 cm above the roof surface and also in the substrate. We showed that under well-watered conditions, the air above the green roof, compared to the white gravel roof, was colder at night and warmer during the day. This suggests that extensive sedum-covered green roofs might help decrease air temperatures at night, when the urban heat island is strongest, but possibly contribute to high daytime temperatures. The average 24 h effect of sedum-covered green roof was a 0.2 °C increase of air temperature 15 cm above the ground. During a dry year the examined green roof exhibited behavior similar to conventional white gravel roof even exhibited slight cooling effect in late afternoon. Interestingly, the pattern of soil temperature remained almost the same for both dry and well-prospering green roofs, colder during the day and warmer at night. Highlights: Extensive sedum-covered green roofs increase the air temperature during the day and exhibit weak cooling effect at night. The effect of a different initial soil moisture contents showed a tipping point around 0.12 m 3 m −3 . Under an extremely dry conditions, a nocturnal cooling effect is no longer apparent above the green roof. Measurements 30 cm above roof level are influenced more by the surrounding area than by the properties of the roof surface.